2012
DOI: 10.1158/0008-5472.can-12-0684
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Resistance to Tamoxifen Is Associated with Loss of the Type I Insulin-like Growth Factor Receptor: Implications for Breast Cancer Treatment

Abstract: The role of the insulin-like growth factor (IGF) system in breast cancer is well defined, and inhibitors of this pathway are currently in clinical trials. The majority of anti-IGF1R clinical trials are in estrogen receptor–positive patients who have progressed on prior endocrine therapy; early reports show no benefit for addition of IGF1R inhibitors to endocrine therapy in this setting. In this study, we examined the effectiveness of IGF1R inhibitors in vitro by generating tamoxifen-resistant (TamR) cells. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
101
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 37 publications
11
101
0
1
Order By: Relevance
“…4B). Our observations precisely define the mechanisms underlying the paradoxical finding in vivo that acquired resistance to TAM is associated with loss of total IGF-1R (34, 37, 40) but keep (40) or gain of phosphorylated IGF-1R (34, 37). In contrast to the result that the non-genomic action of ER can rapidly (within minutes) activate IGF-1Rβ (27), we detected increased phosphorylation of IGF-1Rβ by 4-OHT after 24 hours (Fig.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…4B). Our observations precisely define the mechanisms underlying the paradoxical finding in vivo that acquired resistance to TAM is associated with loss of total IGF-1R (34, 37, 40) but keep (40) or gain of phosphorylated IGF-1R (34, 37). In contrast to the result that the non-genomic action of ER can rapidly (within minutes) activate IGF-1Rβ (27), we detected increased phosphorylation of IGF-1Rβ by 4-OHT after 24 hours (Fig.…”
Section: Discussionmentioning
confidence: 62%
“…Membrane-associated growth factor receptors, such as IGF-1R are another permissive components resulting in TAM resistance (34-37). IGF-1R is regulated by E 2 in an ER-dependent manner (19, 38).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, 4-OHT is able to simultaneously enhance the non-genomic activity of ER and activates focal adhesion molecules to increase phosphorylation of IGF-1R [11,32] . Our observations precisely define the mechanisms underlying the paradoxical finding in vivo that acquired resistance to tamoxifen is associated with lower levels of total IGF-1R [11,17,28,33] but keep [33] or gain of phosphorylated IGF-1R [11,17,28] . Together, these results demonstrate that 4-OHT exerts distinct functions on nuclear ER and membrane-associated ER, which differentially affects the function of IGF-1R.…”
Section: Serms Increase the Crosstalk Between Er And Membrane Functiomentioning
confidence: 64%
“…It is well known that cytoplasmic adapter proteins have the capacity to provide docking sites for the redistribution of a low percentage of ER [26] that functionally associates with the cell membrane, and facilitate the crosstalk between the ER and growth factor receptors [26,27] . Accumulating evidence has suggested that growth factor receptors, such as epidermal growth factor receptor (EGFR) [27] , IGF-1R [11,28,29] , and HER-2 [30] are implicated in acquired SERM resistance, but its precise contributions are not well understood. In our SERM-resistant cell model, levels of IGF-1R are increased by E2 in an ER-dependent manner [10,11] .…”
Section: Serms Increase the Crosstalk Between Er And Membrane Functiomentioning
confidence: 99%
“…So far, the mechanism of choosing classical or non-classical pathway remains unknown. Oestrogen receptors also affect the activation of growth factors, such as EGFR, HER2/Neu and IGFR [15][16][17][18][19]. Sawczuk el al.…”
Section: Topical Oestrogen Therapymentioning
confidence: 99%